(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
Today, social networks have become an integral part of society. Almost every activity is connected to them. Through social networks, one can find sufficient information on any topic, exchange ideas, and gain knowledge. However, due to the vastness of the network, establishing full control over it is a challenging issue. This article discusses the threats and information attacks frequently encountered by users. The information presented below helps users avoid becoming victims of such dangers.